(untitled) (Journal of Forensic Medicine & Toxicology, 2018)
Using a sample of north Indian assault cases, this study examines the relationship of violence with gender. Male to female ratio was 2.7. Most of the cases were in the age group of 21-30 years followed by age group 31-40 years for both males and females. Considering the monthly variation, males were commonly assaulted in October and November, whereas females were commonly assaulted in May and November. Males were mostly assaulted during night from 10pm to 12 midnight; whereas females were mostly assaulted during afternoon from 12noon to 2pm. Males involved mostly residents of rural areas, however females were predominantly from urban areas.